2017
DOI: 10.1177/1941738117745806
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Fear Predicts Functional Performance and Second ACL Injury After ACL Reconstruction and Return to Sport: A Pilot Study

Abstract: Self-reported fear of movement/reinjury after ACLR at the time of RTS may be an important measure to incorporate into discharge criteria prior to release to return to pivoting and cutting sports after ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
190
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(230 citation statements)
references
References 38 publications
8
190
0
Order By: Relevance
“… 10 11 12 Paterno et al, in their retrospective study on 40 ACL-Rs, concluded that patients with greater fear of reinjury were four times more likely to gain lower level of activity, seven times more likely to have a single-hop limb asymmetry, and six times more likely to have a deficit of quadriceps strength greater than 90% compared with the contralateral limb. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 10 11 12 Paterno et al, in their retrospective study on 40 ACL-Rs, concluded that patients with greater fear of reinjury were four times more likely to gain lower level of activity, seven times more likely to have a single-hop limb asymmetry, and six times more likely to have a deficit of quadriceps strength greater than 90% compared with the contralateral limb. 13 …”
Section: Introductionmentioning
confidence: 99%
“…We anticipated this in light of research linking psychological factors to movement characteristics in sport athletes and trauma exposure to acute stress reactions, 19 physical health, 21 and pain. 22 As alluded to earlier, self-reported fear predicted physical performance in participants returning to sport after surgery, 15 and psychological distress was linked to injury prevalence in adult populations. 17 Our findings suggest that such mind-body connections may be extrapolated to FM characteristics in a military population.…”
Section: Discussionmentioning
confidence: 89%
“…14 Yet these are unlikely to be the sole determinants. In fact, psychological antecedents of physical performance 15 and injury risk 16 are increasingly being recognized in athletes. In one such study, 15 self-reported fear predicted hop-test performance and isometric leg strength in athletes returning to sport after anterior cruciate ligament reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…115,116 Effective surgical interventions are available to repair these injuries and restore short-term function and mobility to preinjury performance levels, but surgical repair does not prevent the early development and rapid progression of PTOA in the knee joint. 117 Furthermore, significant deficits in patient-reported outcomes, 118 neuromuscular function, 119 biomechanical movement patterns, 120 and psychosocial factors 121,122 have been noted even after patients have undergone ACLR and completed a full course of therapy.…”
Section: Secondary and Tertiary Risk And Preventionmentioning
confidence: 99%